Answer:
(n-5)^2 - (6n-35)=(n-10)(n-6)
-----------
- n²-10n+25-6n+35 =
- n²-16+60 = n²- 10n - 6n + 60 =
- n(n-10) - 6(n-10) =
- (n-10)(n-6)
The anwser is 0.083 a bunch of threes follow but the aren't important all you need to do is round which that should be rounded enough.
Answer:
2.3 2.389 2.39 2.4 2.41
Step-by-step explanation:
2.3<2.389 (2,39)<2.39<2.4<2.41
Answer:
-161
Step-by-step explanation:
![f(x)=-3x^2+3x+7\\f(8)=-3(8)^2+3(8)+7\\f(8)=-3(64)+24+7\\f(8)=-192+31\\=-161](https://tex.z-dn.net/?f=f%28x%29%3D-3x%5E2%2B3x%2B7%5C%5Cf%288%29%3D-3%288%29%5E2%2B3%288%29%2B7%5C%5Cf%288%29%3D-3%2864%29%2B24%2B7%5C%5Cf%288%29%3D-192%2B31%5C%5C%3D-161)
Answer:
y=1/5x+7
Step-by-step explanation:
just checked it on paper